2016
DOI: 10.18235/0000475
|View full text |Cite
|
Sign up to set email alerts
|

Situación de salud, nutrición y saneamiento entre los niños menores de 12 meses en el Distrito 8 de El Alto: Resultados de encuesta de línea base del Programa de Mejoramiento Nutricional en El Alto, Bolivia fase II

Abstract: Características de la vivienda Vivienda.-Mayoritariamente sobresalen las casas como tipo de vivienda en el 24% de los casos, con una marcada incidencia de declaración de cuartos o habitaciones sueltas del 73%. La incidencia de piso de material firme es del 93% entre los hogares. Un 85% de los hogares utiliza gas licuado a través de garrafa para cocinar. Agua, saneamiento y condiciones del ambiente Acceso a agua.-El 81% de los hogares cuenta con acceso para consumo y uso en el hogar a través de agua de red prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Ex ante, the study was powered (power 0.80 and significance level 0.05) to detect a 5 percentage-point change in stunting or 0.13 SD change in height-for-age z score. 22 Ex post estimates on the endline sample, accounting for attrition, yield a minimum detectable effect size of 0.14 SDs in height-for-age z scores for the intent to treat sample.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…Ex ante, the study was powered (power 0.80 and significance level 0.05) to detect a 5 percentage-point change in stunting or 0.13 SD change in height-for-age z score. 22 Ex post estimates on the endline sample, accounting for attrition, yield a minimum detectable effect size of 0.14 SDs in height-for-age z scores for the intent to treat sample.…”
Section: Methodsmentioning
confidence: 96%
“…Based on evidence from the first phase, CSRA started a renewed intervention based on formative research that identified existing beliefs, preferences and practices that represented potential barriers to adequate child nutrition. 22 23 The redesigned intervention introduced changes in the structure of the home visits, eliminated growth monitoring activities from home visit protocols and developed a new approach for the delivery of the culturally adapted messages.…”
Section: Methodsmentioning
confidence: 99%